Analysis of the Arabic Language Textbook for Tenth Grade at Mohammadiyah Higher Vocational School issued by the Council of Primary and Secondary Education on the Central Leadership of Muhammadiyah based on BSNP Standards - Sulaeman, Arief Yahya; Ismaili, Jalal (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the Arabic textbooks for class X of SMK Muhammadiyah published by the Elementary and Secondary Education Council of the Central Executive of Muhammadiyah based on BSNP standards in terms of content/material feasibility, presentation feasibility, linguistic feasibility and graphic feasibility in textbooks. This research is a descriptive qualitative approach with a literature study type with primary data sources from Arabic books in class X published in 2019. In this study, documentation, interview, and questionnaire methods were used as data collection methods and combined with descriptive analysis as analysis methods. So, the data analysis technique used in this study is content analysis. As a result of this study, the feasibility aspect of Book Content received an average score of 4.3, showing good compatibility with the curriculum and learning objectives. The feasibility aspect of the Book Presentation received an average score of 3.6, this book balances the presentation of the material, although some aspects require improvement to improve student understanding. The eligibility aspect of Book Linguistics gets an average score of 3.3 indicating a language that corresponds to the student's level of development and the right choice of words, although there are some terms that are difficult to understand. The feasibility aspect of Book Graphics scored an average of 3.8, indicating good graphic quality although some illustration elements still need improvement.